When positive thinking is not enough: The role of the HDML framework in explaining complex behavior in RFT - Simões, Aline Souza; Ferreira, Tiago Alfredo da Silva (Perspectivas em Análise do Comportamento, 2021)
A central thesis of Relational Frame Theory states that reports and self-reports not only describe the world, both public and private, but also transform the functions of the described world. Creating new verbal contexts for the occurrence of public and private events is one of the main strategies of Acceptance and Commitment Therapy. In a clinical perspective, if we consider that reports and self-report promote stimulus functions that are not very helpful for the client to build a life worth living, would the alternative be to give them new reports and self-reports? If we consider self-reports as thoughts, would the clinical intervention consist then of a type of “thought re-programming”? To answer these questions, this paper will discuss the advances in the field of RFT relating to the Hyper-Dimensional Multilevel (HDML) framework and its relevance to the understanding of complex human behavior. To start, we will describe briefly the RFT trajectory from its original proposal until HDML. Then, we will discuss how the dimensions presented in this model are essential to the understanding of clinical intervention based on RFT and we will conclude with some reflections on the relation between basic research in RFT and the development of new therapists.